PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) PADA SISWA KELAS IV DI MI AL HUSNA TANGEN - Tri Utami, Winarti; Nuri Satriyawan, Aziz; Lusyana, Evvy (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2023)
The purpose of this research is to improve the mathematich learning outcomes of students at MI Al Husna Tangen through the Indonesia Realistic Mathematics Education Approach. This research is a Classroom Action Research conducted in two cycles. This research was conducted on fourth grade students of MI Al Husna Tangen for the 2020/2021 Academic Year with a total of 30 students in fructional material. Data collection using the end of the cycle test. Data analysis uses averages and percenteges. The results of the study show that this approach is able to improve students mathematics learning outcomes. It can be proven that: 1. An increase in the average student mathematics learning outcomes, namely in the pre-cycle of 61.90 to 67.07 in cycle I and 78.27 in clycle II; 2. The increase in the percentage of students who complete learning, namely in the pre-cycle of 33.33% to 56.67% in clycle I and 83.33% in clycle II. Thus it can be shown that there is an increase in mathematics learning outcomes with the application of the Indonesian Realistic Mathematics Education Approach.